From fasting to feasting: embracing Ramadan & Raya 2025 - Syafie, Aleyya Mardhiyyah; Zamery, Muhammad ‘Izzuddin (Faculty of Pharmacy, 2025)
The holy month of Ramadan 1446H FROM FASTING TO FEASTING: Embracing Ramadhan & Raya 2025 was marked with great enthusiasm and spiritual reflection at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam, as the Society of Pharmacy Students (SOPHYS) 2024/2025 and the Faculty of Pharmacy Student Secretariat (SMF) 2024/2025 successfully organised their annual programme, From Fasting to Feasting: Embracing Ramadan & Raya. The initiative aimed to enrich students’ experiences by fostering religious, educational, and cultural engagement during the sacred period of Ramadan and the festive celebration of Hari Raya.